Malignant psammomatous melanotic schwannoma mimicking adrenal cyst: case report - Aleksandar Zlatarov; Plamena Drenakova; Stefan Mihaylov; Neli Zgurova; Lilyana Petkova; Krasimir D. Ivanov (SpringerOpen, 2022)
Abstract Background Melanotic schwannoma is a melanin producing nerve sheath tumors. Rarely, it can be associated with psammoma bodies, called psammomatous melanotic schwannoma. Psammomatous melanotic schwannomas are associated in up to 10% of the cases with Carney's syndrome. The rarity of the lesion, which may present at different localizations create difficulty in placing a correct initial diagnosis. Definitive diagnosis is made after complete tumor excision and pathomorphological evaluation. The prognosis depends on the anatomical localization, local invasion and presence of a high mitotic index. The main pathomorphological differential diagnosis includes schwannomas and other melanin producing tumors as melanoma. Case presentation We present a case of an 11-year-old female with cystic lesion adjacent to right adrenal gland, mimicking adrenal cyst. Ultrasound guided biopsy was undertaken due to the cystic appearance of the formation and the lack of certain diagnosis from the non-invasive diagnostic tests. No signs of cellular and nuclear atypism were observed. The diagnosis of benign endothelial cyst with spontaneous hemorrhage was suggested. The patient underwent transabdominal laparoscopic adrenalectomy en-bloc with the cyst to prevent spillage of the cyst content due to the intimate adhesion of the lesion to the adrenal gland and vena cava inferior. Pathomorphological examination revealed malignant psammomatous melanotic schwannoma. The adrenal gland was intact with no tumor infiltration. The patient was followed up on the 1st and 2nd month afterwards the surgery by MRI with no signs of local recurrence and postoperative complications. Conclusion Psammomatous melanotic schwannoma near adrenal gland are rare and present difficulty with exact preoperative diagnosis. Complete resection should always be provided. Laparoscopic surgery is feasible if radical excision is not compromised. Long-term follow-up and Carney's syndrome surveillance after complete excision are recommended especially in young patients.